2017
DOI: 10.1016/j.envres.2017.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of infant exposure to persistent organic pollutants and mercury via dietary intake in a central western Mediterranean site (Menorca Island)

Abstract: In this research the levels of organochlorine compounds (OCs) and mercury (Hg) in several food items from Menorca Island were presented. The dietary exposure assessment was performed in children population from the island. Finally, body burden of OCs and Hg in these infants were associated with their dietary intakes of the selected food items. The dietary exposure to persistent pollutants by children population from Menorca Island was assessed. The concentrations of 11 organochlorine pesticides, 6 polychlorina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
2
14
0
2
Order By: Relevance
“…The Hg concentrations observed in the present study were consistent with previous results reported in the same organisms from the Adriatic Sea (Storelli and Barone, 2013;Storelli et al, 2007), Farwa Island (Lybian coast; Banana et al, 2016), the Gulf of Lion (Torres et al, 2015;Cresson et al, 2014), the Aegean Sea (Yabanli and Alparslan, 2015), Menorca (Junqué et al, 2017) and deep-sea sites from the Mediterranean basin (Koenig et al, 2013;Naccari et al, 2015).…”
Section: Mercurysupporting
confidence: 93%
See 2 more Smart Citations
“…The Hg concentrations observed in the present study were consistent with previous results reported in the same organisms from the Adriatic Sea (Storelli and Barone, 2013;Storelli et al, 2007), Farwa Island (Lybian coast; Banana et al, 2016), the Gulf of Lion (Torres et al, 2015;Cresson et al, 2014), the Aegean Sea (Yabanli and Alparslan, 2015), Menorca (Junqué et al, 2017) and deep-sea sites from the Mediterranean basin (Koenig et al, 2013;Naccari et al, 2015).…”
Section: Mercurysupporting
confidence: 93%
“…With the exception of HCB the concentrations of the organochlorine compounds from fish captured near the Canary Islands were lower than those in the Balearic Islands analysed in the present study (Table 2). The average concentrations of HCB, total HCHs and total DDTs in fish captured nearby the Balearic Islands are quite similar than those observed in fish captured near Menorca (Junqué et al, 2017). However, the PCB concentrations are higher in the present case, 2.4 ng/g ww vs. 1.7 ng/g ww (Table 2).…”
Section: Occurrence Of Organochlorine Compoundssupporting
confidence: 71%
See 1 more Smart Citation
“…The principal source of exposure to these compounds among the general population is diet. They are found mainly in animal products, including meat, fish, dairy products and eggs (Junqué et al, 2017;Llobet et al, 2003;Martí-Cid et al, 2007).…”
Section: Organohalogen Compound Distributionsmentioning
confidence: 99%
“…Consuming large quantities of seafood has been identified as a primary method for environmental exposure to methyl mercury [65]. Although the pathway through which mercury enters the ecosystem has not been discovered, bioaccumulation of this heavy metal has been observed in shellfish and tuna [65,68,69].…”
Section: Mercurymentioning
confidence: 99%